Diffuse idiopathic neuroendocrine cell hyperplasia: an unusual cause of breathlessness and pulmonary nodules - Tippett, V M (BMJ Publishing Group, 2010)
A 66-year-old woman presented with dry cough and subsequent intermittent breathlessness and wheeze. During this time she was treated by her general practitioner for chronic obstructive pulmonary disease. When her symptoms worsened and her lung function had deteriorated, a high resolution CT scan was undertaken. This showed bilateral fine nodules. Investigations did not support a diagnosis of vasculitis and sarcoidosis was suspected. A lung biopsy was performed that showed diffuse idiopathic neuroendocrine cell hyperplasia. At follow-up, to date, the patient remains symptomatic but has not progressed or developed a carcinoid tumour.